STRATEGIC TA’AWUN AND FASTABIQUL KHAIRAT PARTNERSHIPS FOR SUSTAINABLE COMPETITIVE ADVANTAGE AMONG SMALL AND MEDIUM ENTERPRISES IN THE MUSLIM WORLD - Suhaimi Mhd. Sarif (Asian Academy of Management Journal, 2019)
Strategic ta’awun (cooperation) and fastabiqul khairat (competing for goodness) are two partnership concepts from Islamic perspectives to enable for sustainable competitive advantage with spiritual synergy. The spiritual synergy rooted in the reciprocal norms, motivation, and determination of the operators in making successful entrepreneurial ventures not only for profitability, but for humanity and environmental benefits. This research explores the effects of strategic ta’awun and fastabiqul khairat partnerships among small and medium enterprises (SMEs) in the Muslim world to attain and sustain competitive advantage. Strategic ta’awun and fastabiqul khairat are part of the Islamic teachings practiced by Muslim society along with obligatory deeds such as prayers, zakat, and hajj. This study postulates that the spiritual reciprocal power in strategic ta’awun enables for unity and synergy among SMEs in Muslim world. Likewise, the reciprocal power of fastabiqul khairat among SMEs enables Muslim society to venture into model of entrepreneurial, urbanised, and sustainable society. The study interviewed five key SMEs owners representing different geographical locations (Southeast Asia, South Asia, Middle East Asia, North America, and Europe). Indeed, the informants argued that the spiritual reciprocal norm in strategic ta’awun occurred through collaboration and partnerships among SMEs for goodness (fastabiqul khairat) in terms of sharing of expertise, contacts, and commercial projects. This situation allows them to strengthen their competitive advantages in competing with consortium of competitors from different regions. The study suggests the future research to employ case study method for more contextual insights.